An Analysis of Lexical Borrowing Used By The Eighth Semester Students of English Language Education in Social Media - ., Ni Kadek Yuni Artini; ., Prof. Dr. Ni Nyoman Padmadewi, M.A.; ., Kadek Sintya Dewi, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengidentifikasi jenis peminjaman leksikal dan untuk menyelidiki makna dari setiap penggunaan pinjaman leksikal di media sosial terutama di grup Line oleh mahasiswa semester delapan Jurusan Pendidikan Bahasa Inggris. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek dari penelitian ini adalah mahasiswa semester delapan Jurusan Pendidikan Bahasa Inggris. Instrumen yang digunakan dalam penelitian ini adalah smartphone. Data dikumpulkan dengan mengambil tangkapan layar dari percakapan online yang mengandung leksikal borrowing. Data kemudian diururtkan, diklasifikasi, dianalisis, didiskusikan dan disimpulkan berdasarkan klasifikasi teori yang diusulkan oleh Capuz. Hasil dari penelitian ini menunjukkan bahwa ada tiga jenis peminjaman leksikal dari 50 jenis kata dari peminjaman leksikal yang dihasilkan oleh mahasiswa semester delapan. 30 jenis kata termasuk importation, 18 jenis kata termasuk loanblend dan 2 jenis kata termasuk loan translation. Peminjaman leksikal tetap memiliki makna secara harfiah dan beberapa memiliki makna secara tersirat. Kata Kunci : Sosial Media, Jenis Peminjaman Leksikal, Makna Peminjaman leksikal This study aimed at identifying the types of lexical borrowing and to investigate the meaning of each lexical borrowing in social media especially in Line group chatting by the eighth semester students of English Language Education. This study was descriptive qualitative research. The subjects of this study were the eighth semester students of English Language Education. The instrument used in this study was mobile phone. The data were collected by taking the screenshot of any conversation containing lexical borrowing. The data were listed, classified, analyzed, discussed and summarized based on the theory classification proposed by Capuz. The result of this study showed that there were three types of lexical borrowing from fifty (50) words of lexical borrowing produced by the eighth semester students. Thirty (30) words belong to importation, eighteen (18) words belong to loanblend, and two (2) words belong to loan translation. The lexical borrowing still have their literal meaning and some have their implied meaning. keyword : Social Media, Lexical Borrowing Types, Lexical Borrowing MeaninG